A Comparative Analysis between Laparoscopic and Open Cholecystectomy at a Tertiary Care Hospital in Patients with Acute Cholecystitis - A V Akulwar; Ajonish Kamble; Neha Bhatt; chandrasekhar Mahakalkar (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Acute cholecystitis is clinically characterized as an episode of acute biliary pain; fever and right hypochondrial tenderness with symptoms persistence exceeding 24 hours. Aims & Objectives: We compared and analyzed open and laparoscopic cholecystectomy in the current study on the basis of the duration of the operation, intra and postoperative complications and the length of hospital stay & return to work.Material and Methods: This was a prospective comparative, randomized hospital-based study performed in patients of 20 - 80 years of age with acute cholecystitis in the Department of General Surgery from July 2019 to January 2021 at SMH&RC, Datta Meghe Medical College Nagpur. Patients were divided randomly into two classes as Open cholecystectomy (60 patients) and laparoscopic cholecystectomy (60 patients). The key assessed outcome was death, peri-operative & post-operative complications; length of hospital stay and wound infection, return to work. The gathered data was statistically analyzed. Results: In both categories, the most common age group was 40-59 years old. The female population (78%) was greater than the male population (22 percent). 1: 3.6 was the male to female ratio. The mean time needed for open cholecystectomy was 53.18 ± 12.74 minutes, while 38.37 ± 6.21 minutes for laparoscopic cholecystectomy, and the difference was statistically important. 2 (3.3 percent) laparoscopic procedures involved conversion to open surgery due to difficult dissection, bleeding & blurred vision. In terms of postoperative pain (VAS > 4), hospital stay period and return to work, laparoscopic cholecystectomy had better outcomes than open cholecystectomy and the difference was statistically important. In Open Cholecystectomy patients, wound infection, post-operative paralytic ileus was substantially greater. There were 2 patients with wound dehiscence from open cholecystectomy. No significant morbidity or any mortality during the study period was reported.Conclusion: Laparoscopic cholecystectomy provides decisive advantages over open cholecystectomy in acute cholecystitis (e.g. shorter time of surgery, fewer post-operative complications, less paralytic ileus, less analgesic use, early discharge and mobilization).